Melioidosis: an emerging infectious disease. - Raja, N.S.; Ahmed, M.Z.; Singh, N.N. (Medknow Publications, 2005)
Infectious diseases account for a third of all the deaths in the developing world. Achievements in understanding the basic microbiology, pathogenesis, host defenses and expanded epidemiology of infectious diseases have resulted in better management and reduced mortality. However, an emerging infectious disease, melioidosis, is becoming endemic in the tropical regions of the world and is spreading to non-endemic areas. This article highlights the current understanding of melioidosis including advances in diagnosis, treatment and prevention. Better understanding of melioidosis is essential, as it is life-threatening and if untreated, patients can succumb to it. Our sources include a literature review, information from international consensus meetings on melioidosis and ongoing discussions within the medical and scientific community.